FORMULASI KRIM WAJAH EKSTRAK PELEPAH POHON AREN (Arenga pinnata Merr.) SEBAGAI ANTI ACNE - Fauzi, Rizky Mohammad; Nugraha, Davit; Wahlanto, Panji (Jurnal Farmasi & Sains Indonesia, 2022)
Aren (Arenga pinnata Merr.) is a biological resource believed to have antioxidant abilities and is easily found throughout Indonesia. It is widely used by the populace, for example in midrib flour as a traditional medicine to relieve itching and scars on the skin. The purpose of this study was to determine whether the palm leaf extract (Arenga pinnata Merr.) could be formulated into cream preparations and was of good quality. The research method used is experimental by formulating the extract into three formulations, namely the extract concentration of 1%, 3%, 5%. Data analysis was performed using qualitative analysis including organoleptic test, homogeneity test, and quantitative analysis including pH test, dispersion test, adhesion test, viscosity and using one-way ANOVA statistics. The results of the analysis showed that there was no significant difference in the concentration of palm midrib cream in pH with a sig value of 0.542 (sig. > 0.05), a dispersion of 0.504 (sig. > 0.05) and a Adhesion of 0.717 (sig. > 0.05) gave > 0.05) and the viscosity meets the standard of good cream viscosity which is between (2000 - 50000 cps). Data analysis of the results showed that the three variations of extracts could be formulated into cream preparations and had quality standards for cream preparations that met the requirements, there was no effect of variations in the concentration of arene (Arenga pinnata Merr.) on the physical quality of cream preparations. The best wording is found in F2 (3%). Further research is expected to modify the formula for preservatives and fragrance additives, create new dosage forms such as lotions.